Ex ante impact assessment and seasonal climate forecasts: status and issues - Thornton, Philip K. (Inter-Research Science Center, 2006)
The field of ex ante impact assessment has been receiving increasing attention in recent years, due in part to the rapidly changing nature of funding for agricultural research and the shifts that have occurred in what is expected of the international agricultural research community. Ex ante studies are often carried out to provide information to assist in the allocation of scarce research resources to activities that are efficient in some way, or that best match donors’ development objectives. In practice, impact assessment is often contentious and usually difficult. Despite this, a wide range of tools has been developed for ex ante impact assessment, and these are used routinely in many different areas. Here, various ex ante impact assessment methods are outlined that may be used to provide aggregated information at the scale of the region or society. Also discussed is how technological and policy changes associated with seasonal climate forecasts in developing countries can be assessed through a combination of these methods. Recent developments in quantitative modelling, and the availability of high-resolution regional and global data sets, could in the future contribute significantly to the identification of niches where seasonal climate forecasts could help vulnerable people cope with variability, with concomitant impacts on the alleviation of poverty.